1993
DOI: 10.1302/0301-620x.75b6.8245073
|View full text |Cite
|
Sign up to set email alerts
|

Cement-within-cement revision hip arthroplasty

Abstract: We reviewed 19 revision hip arthroplasties in which the new femoral component had been recemented into the old, intact cement mantle. The mean time from the first operation to revision was 64 months and the average follow-up was 59 months. There were 7 excellent, 1 1 good, and one fair result. No femoral component had been revised for loosening and all the stems appeared radiographically stable. Cornplications included intraoperative perforation of the femur on two occasions and one dislocation. The use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 6 publications
4
56
2
2
Order By: Relevance
“…Isolated acetabular revision represents about 10% of revision hip arthroplasty [3] and only few reports [4,12,13] have been published. In some instances, retention of the stem may be beneficial as it may result in reduced morbidity, complications, blood loss, operative time, and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated acetabular revision represents about 10% of revision hip arthroplasty [3] and only few reports [4,12,13] have been published. In some instances, retention of the stem may be beneficial as it may result in reduced morbidity, complications, blood loss, operative time, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…For these stems, a titanium sleeve [16] has been proposed for use with an alumina head on the old Morse taper. Another solution to change the femoral head could be to use the cement-within-cement technique [13] in isolated cup revision presenting with a stable stem. This technique allows for a better visualization of the acetabulum and prevents Morse taper damage.…”
Section: Discussionmentioning
confidence: 99%
“…2a, b), acetabular failures in which the surgery is easier if the femoral component is taken out, conversion from a cemented hemiarthroplasty to a THA and recurrent dislocation (Fig. 3a, b) [17,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…From a biomechanical viewpoint, this technique was validated by studies reported by Greenwald et al [12]. Although the method is about to turn 20 years old, the results of the cement within cement (CWC) technique have been described in the literature by few authors [17,18,20,22].…”
Section: Introductionmentioning
confidence: 98%
“…This technique is used to revise a failed femoral component, or to aid in the exposure of an isolated acetabular revision when a monoblock femoral component is removed and recemented into the intact cement mantle [3]. We report the use of the arthroscope for the assessment of the integrity of the cement mantle, to assess the removal of the previously inserted distal cement centralizer, and to assist in the preparation of the cement mantle for recementation.…”
Section: Introductionmentioning
confidence: 99%